2005
DOI: 10.1042/bj20041066
|View full text |Cite
|
Sign up to set email alerts
|

The membrane-anchored serine protease, TMPRSS2, activates PAR-2 in prostate cancer cells

Abstract: TMPRSS2 is a type II transmembrane-bound serine protease that has gained interest owing to its highly localized expression in the prostate and its overexpression in neoplastic prostate epithelium. Once activated, the serine protease domain of TMPRSS2 is released from the cell surface into the extracellular space. PAR (protease-activated receptor)-2 belongs to a family of G-protein-coupled receptors (PAR-1-4) that are activated by specific serine proteases, which are expressed in many normal and malignant cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
144
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 33 publications
2
144
2
4
Order By: Relevance
“…In sum, these results are consistent with the hypothesis that KLK2 and PSA are positively selected in the context of sexually antagonistic coevolution, with the functional roles of the genes being of general importance to both the risk and somatic evolution of cancer. Transmembrane protease serine 2 has been identified as an important gene in the development of prostate cancer, with overexpression in neoplastic prostate epithelium [70]. The serine protease domain of TMPRSS2 is released into the extracellular fluid, and interacts there with a G-coupled receptor (PAR-2), which contributes to tumor metastasis.…”
Section: Mta1mentioning
confidence: 99%
“…In sum, these results are consistent with the hypothesis that KLK2 and PSA are positively selected in the context of sexually antagonistic coevolution, with the functional roles of the genes being of general importance to both the risk and somatic evolution of cancer. Transmembrane protease serine 2 has been identified as an important gene in the development of prostate cancer, with overexpression in neoplastic prostate epithelium [70]. The serine protease domain of TMPRSS2 is released into the extracellular fluid, and interacts there with a G-coupled receptor (PAR-2), which contributes to tumor metastasis.…”
Section: Mta1mentioning
confidence: 99%
“…By use of the PAR-2 antagonist Phe-Ser-Leu-Leu-Arg-Tyr-NH 2 it was found that matriptase and TMPRSS2 can activate PAR2, which suggests an additional link between a membrane-anchored serine protease and prostate tumor metastasis. However, further studies should be conducted if excessive amount of TMPRSS2 in intracellular space may play a functional role in prostate tumorigenesis in addition to cell surface protease activity 9,13,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, given the widespread distribution of PAR 2 and the restricted expression of trypsin I/II to the pancreas, where activity is tightly controlled by endogenous inhibitors, the proteases that activate PAR 2 in tissues other than the pancreas and intestine remain to be identified. Other proteases that can cleave PAR 2 at Arg 36 2Ser 37 include trypsin IV (mesotrypsin) (17,18), tryptase (19,20), coagulation factors VIIa and Xa (21), acrosin (22), granzyme A (23), membrane-type serine protease 1 or matriptase (24), TMPRSS2 (25), and kallikrein 2, 4, 5, 6, and 14 (26 -29). These proteases would be expected to trigger the same canonical signaling events as trypsin I/II, leading to similar physiological outcomes.…”
mentioning
confidence: 99%